Chronic dimethomorph exposure induced behaviors abnormalities and cognitive performance alterations in adult zebrafish (Danio rerio) - Wong, Heong-Ieng; Audira, Gilbert; Chen, Hsiu-Chao; Feng, Wen-Wei; Suryanto, Michael Edbert; Saputra, Ferry; Kurnia, Kevin Adi; Casuga, Franelyne P.; Hsiao, Chung-Der; Hung, Chih-Hsin (Toxicology reports, 2025)
Dimethomorph is a systematic fungicide that inhibits sterol synthesis in fungi and unfortunately, there was only scarce data regarding its toxicity. Therefore, considering its extensive application in agriculture and its presence in food residues and the environment, its toxicities in non-target organisms, including aquatic animals, are required to be evaluated since they are sensitive indicators of ecological change. In this study, we evaluated the toxicities of dimethomorph after chronic exposure to adult zebrafish (Danio rerio) by conducting various behavioral assays, a passive avoidance test, and biochemical assays by ELISA. From the results, ∼ 2 weeks exposure to dimethomorph caused lower locomotion, aggressiveness, and conspecific social interaction, and more robust predator avoidance behaviors. Furthermore, alterations in color preferences and short-term memory loss were also observed in the treated fish. In helping to elucidate the mechanism, the expression level of several important neurotransmitters in the brain tissue was measured. Interestingly, increment in several biomarkers, including serotonin, kisspeptin, epinephrine, norepinephrine, and dopamine was observed in the treated group along with a slight increase in other tested neurotransmitters, which were catalase, acetylcholine, and melatonin, which might play a role in the observed behavior alterations. Nevertheless, the results from the current study suggested possible alterations in the central nervous system by dimethomorph, and thus, consideration is required prior to the usage of this fungicide in the agricultural fields surrounding natural freshwater reservoirs.